2020
DOI: 10.1080/08897077.2019.1635966
|View full text |Cite
|
Sign up to set email alerts
|

Posting, Texting, and Related Social Risk Behavior While High

Abstract: Background: Posting on social media can have lasting consequences in one's social life and career. Research has not yet focused on social media or more modern forms of communication as social risk factors for individuals high on drugs. This study aims to examine prevalence and correlates of engaging in social media posting and related behavior while high. Methods:We examined data from 872 adults (39.8% female) who were surveyed entering electronic dance music (EDM) parties in New York City and reported lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Further information about study methods can be found elsewhere. 8 A few weeks after human subjects research requiring contact with participants was halted, we obtained IRB approval to recruit and survey participants online. This method was proposed to: 1) continue to examine drug use in this population during the crisis, and 2) examine how drug use behavior has changed during COVID-related social distancing.…”
Section: A Brief Description Of Our Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Further information about study methods can be found elsewhere. 8 A few weeks after human subjects research requiring contact with participants was halted, we obtained IRB approval to recruit and survey participants online. This method was proposed to: 1) continue to examine drug use in this population during the crisis, and 2) examine how drug use behavior has changed during COVID-related social distancing.…”
Section: A Brief Description Of Our Studymentioning
confidence: 99%
“…Thus far, we have surveyed some 1,100 participants, with our overall target being 2,080 participants by early 2021. Further information about study methods can be found elsewhere 8…”
Section: A Brief Description Of Our Studymentioning
confidence: 99%